The Application of Self-evaluation in English Reading Teaching - Yixi, Pan (International Journal of Humanities and Education Development (IJHED), 2023)
Self-evaluation is an important part of formative evaluation. Students' self-evaluation can not only enable students to find the problems in their learning and timely understand the weak links in their learning, but also enable teachers to clearly grasp the true ideas of students and implement targeted teaching according to the feedback given by students.